What You Need to Know About Cannabis: An Evidence-Based Crash Course for Mental Health Trainees - Thida Thant; Abraham Nussbaum (Association of American Medical Colleges, 2020)
Introduction Although increasing numbers of states are legalizing cannabis for both medical and recreational purposes, health care providers and students report low comfort levels and limited knowledge regarding cannabis, highlighting current deficits in medical training. Methods We developed a structured cannabis curriculum for a general psychiatry residency program at the University of Colorado. In constructing our curriculum, we initially surveyed advanced psychiatry residents and attending psychiatrists in the university outpatient clinic regarding attitudes and approaches to psychiatric patients using cannabis. Prior to implementation in the following year's core curriculum for first-year postgraduates (PGY 1s), pretest assessments evaluated PGY 1s' attitudes towards cannabis use and identified learning expectations, challenges, and confidence levels. After the seminars were completed, residents provided posttest assessments and general course evaluations. Utilizing initial survey information, we constructed a Marijuana and Medicine introduction curriculum for psychiatry PGY 1s. Topics included strains and formulations, pharmacokinetics, the endocannabinoid system, local Colorado laws, monitoring, evidence regarding use in psychiatric disorders, use in pregnancy, and ethical issues. These topics were covered via case-based discussion, interactive quizzes, direct instruction, and facilitated discussion. Results Posttest assessments indicated improvement in trainees' confidence and knowledge base and requests for additional instruction on topics such as adolescent use. Discussion The positive posttest assessments support the value of incorporating a cannabis curriculum into psychiatric training. Now in its second year, the course has been expanded to 4 hours. As cannabis is medicalized, it is increasingly important that psychiatrists be able to knowledgably counsel their patients.